2018
DOI: 10.3389/fnbeh.2018.00035
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Oxytocin Release Eliminates In-Group Bias in Monetary Transfers With Perspective-Taking

Abstract: Oxytocin (OT) has been shown to facilitate trust, empathy and other prosocial behaviors. At the same time, there is evidence that exogenous OT infusion may not result in prosocial behaviors in all contexts, increasing in-group biases in a number of studies. The current investigation seeks to resolve this inconsistency by examining if endogenous OT release is associated with in-group bias. We studied a large group of participants (N = 399) in existing groups and randomly formed groups. Participants provided two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Our group ran laboratory experiments to assess how positive and negative citizenship behaviors in simulated work settings affected neurophysiology, motivation, and productivity ( Alexander et al, 2018 ; Terris et al, 2018 ; Kraig et al, 2019 ; Johannsen and Zak, 2020 ). We then gained permission from a set of businesses and nonprofit organizations to measure employees’ neurophysiology, motivation, and productivity in their workplaces ( Zak, 2017 ).…”
Section: Theorymentioning
confidence: 99%
“…Our group ran laboratory experiments to assess how positive and negative citizenship behaviors in simulated work settings affected neurophysiology, motivation, and productivity ( Alexander et al, 2018 ; Terris et al, 2018 ; Kraig et al, 2019 ; Johannsen and Zak, 2020 ). We then gained permission from a set of businesses and nonprofit organizations to measure employees’ neurophysiology, motivation, and productivity in their workplaces ( Zak, 2017 ).…”
Section: Theorymentioning
confidence: 99%
“…These levels might be considerably different when people attend religious services. Recent research has shown that social interactions, both religious and secular, that cause the release of OXT, eliminated in-group bias monetary transfers compared to those who did not have an increase in OXT, suggesting that religious attendance may promote prosocial behaviours (70).…”
Section: Discussionmentioning
confidence: 99%
“…We analysed the relationship between OC use and hormones using two previously published datasets 46,47 . Both studies were similar methodologically and the current study includes only women who identified their birth control method.…”
Section: Methodsmentioning
confidence: 99%